The Influence of Materials and Natural Constraints on Mobilisation and Timeliness of Road Improvement Projects in Papua - Sumardi, Sumardi; Mudjanarko, Sri Wiwoho (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2025)
One of the obstacles to construction work in Papua is the delay in implementation time and one of the causes is due to the inadequate condition of the access road to the work site, limited material transport fleet and roadblocks by indigenous peoples at the project site. This study was conducted to further examine the factors causing delays in the completion of road works in Southwest Papua Province, especially in Sorong district. The problem limitations used in this study only focus on factors that affect the Timeliness of Work Implementation as for these factors include: Materials, Natural Constraints and Mobilisation. This research uses Non Probability Sampling technique, which is a sampling technique that provides equal opportunities for each element of the population to become a sample obtained through distributing questionnaires online via google form. The process for processing data from respondent survey results uses SmartPLS software, which is software used for Structural Equation Modeling (SEM) analysis. Based on the results of the Convergent Validity Test, Discriminant Validity Test, Construct Reability Reliability Test and Direct Effect and Indirect Effect Hypothesis Test, the results show that materials have the strongest influence on mobilisation, which ultimately increases the timeliness of work implementation.